A framework for the assessment of the environmental risk posed by pharmaceuticals originating from hospital effluents - Al,Aukidy M; Verlicchi,P; Voulvoulis,N (Science of the Total Environment, 2014)
The consumption of pharmaceuticals is increasing in both hospitals and households. After administration, many compounds enter the water cycle as parent compounds or their metabolites via excretion. Conventional municipal wastewater treatment plants are unable to efficiently remove all the different compounds found in sewage and, consequently, treated effluents are one of the main sources of persistent micropollutants in the environment. Hospital patients are administered relatively high quantities of drugs and therefore hospital wastewaters can consistently contribute to treatment plant influent loads, with the magnitude of environmental risk posed by pharmaceuticals originating from hospital effluents largely unknown. This study has therefore developed a framework to enable authorities responsible for hospital management and environmental health to evaluate such risk, considering site-specific information such as the contribution of human population and hospital sizes, wastewater treatment removal efficiency, and potential dilution in the receiving water body. The framework was applied to three case studies, that are representative of frequent situations in many countries, and findings demonstrated that the degree of risk posed by any compound was site-specific and depended on a combination of several factors: compound concentration and toxicity, compound removal efficiency in the wastewater treatment plant and dilution factor. Ofloxacin, 17α-ethinylestradiol, erythromycin and sulfamethoxazole were identified as compounds of concern and might require management in order to reduce risk.